Sebuah Laporan Kasus Penurunan Fungsi Sistolik Ventrikel Kiri pada Pasien Hamil dengan Tetralogy of Fallot yang Telah Dikoreksi : Kardiomiopati Peripartum atau yang Lainnya? - Gultom, Yosafat Hasiholan Marthin; Martini, Heny (Jurnal Klinik dan Riset Kesehatan, 2025)
Background : Tetralogy of fallot (TOF) is the most common cyanotic congenital heart disease (CHD) worldwide. It is estimated that TOF occupies 5 to 8% of total CHD and twice as many among other CHD simple defect. By far, TOF can only be managed by surgical correction. In most cases, post corrected TOF patients may tolerate pregnancy well. The majority of post corrected TOF patients also have good LV function and just about 23% of them have moderate LV dysfunction. Meanwhile, peripartum cardiomyopathy is one of the cause of LV systolic dysfunction in pregnancy. Case Presentation : A 31-years-old 33 weeks pregnant woman was reffered with chief complain of shortness of breath since 1 month before and preceded with bilateral leg edema (NYHA functional class III). Patient with history of  TOF and was corrected surgically with residual tricuspid regurgitation. Patient with normal left ventricle (LV) systolic function by echocardiography at the second semester of pregnancy and deteriorated at the third semester of pregnancy. Due to the rapid deterioration of LV systolic function, the pregnancy was decided to be terminated by surgery. Patient was treated with bisoprolol, bromocriptine, captopril and warfarin. During the hospitalisation, patient didn’t develop any of arrhytmia or hemodynamic issue. After the termination, patient was with improvement of shortness of breath (NYHA functional class II) and improvement of LV systolic function. Conclusion : A pregnant, post corrected TOF, woman with rapid deterioration LV systolic function and clinical manifestation of heart failure underwent pregnancy termination by surgery. After the termination, patient still with shortness of breath and improvement of LV systolic function.